2008
DOI: 10.1093/jmedent/45.5.891
|View full text |Cite
|
Sign up to set email alerts
|

Novel Arthropod Repellent, BioUD, Is an Efficacious Alternative to Deet

Abstract: For >50 yr, N,N-diethyl-3-methylbenzamide (deet) has been the standard for arthropod repellents and has been an important tool to protect people from disease agents carried by ticks, mosquitoes, and other arthropods. However, some people avoid using deet because of concerns about adverse health effects. In 2007, a new repellent, BioUD, with the active ingredient 7.75% 2-undecanone, originally derived from wild tomato (Lycopersicon hirsutum Dunal f. glabratum C. H. Müll) plants, was registered by the U.S. Envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…For this reason, more acceptable and effective alternatives are needed. We recently described the development of the repellent BioUD (Roe, 2004;Witting-Bissinger et al, 2008;Bissinger et al, 2009aBissinger et al, , 2009b with the EPA-registered compound 2-undecanone. 2-Undecanone is found naturally in the trichomes of wild tomato plants and, along with 2-tridecanone, is used by such plants to resist herbivory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, more acceptable and effective alternatives are needed. We recently described the development of the repellent BioUD (Roe, 2004;Witting-Bissinger et al, 2008;Bissinger et al, 2009aBissinger et al, , 2009b with the EPA-registered compound 2-undecanone. 2-Undecanone is found naturally in the trichomes of wild tomato plants and, along with 2-tridecanone, is used by such plants to resist herbivory.…”
Section: Discussionmentioning
confidence: 99%
“…Bioassays were conducted to determine repellency and the duration of repellent activity on filter paper or cotton cheesecloth using our standard two-choice bioassay (Witting- Bissinger et al, 2008;Bissinger et al, 2009aBissinger et al, , 2009b. On each tested surface, ticks were provided with a choice between the test compound (either 2-tridecanone or 2-undecanone) vs. the ethanol control.…”
Section: Two-choice Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, previous studies from our laboratory have shown that BioUD ® exhibits a level of repellency against ticks that is at least similar to those of 98.1% DEET and 0.5% permethrin under laboratory conditions (Witting-Bissinger et al, 2008;Bissinger et al, 2009aBissinger et al, , 2009b. The results of the current study demonstrate for the first time that BioUD ® under more realistic field conditions and in the presence of host cues and human subjects was as effective as 98.1% DEET and more effective than 0.5% permethrin against nymphal A. americanum.…”
Section: Practical Field-relevant Assays To Evaluate Tick Repellentsmentioning
confidence: 52%
“…As Matthewson et al (1981) and Dautel (2004) explained, laboratory tests in the absence of a host or host cues may result in the overestimation of repellency and incorrect conclusions about the practical value of a compound in host protection. In this regard, the present investigation allows us to compare results of field assay approaches with results of our previous laboratory studies of the repellent action to ticks of BioUD ® , DEET and permethrin on filter paper and cloth (Witting-Bissinger et al, 2008;Bissinger et al, 2009aBissinger et al, , 2009b. The laboratory experiments involved twochoice studies between repellent-treated or untreated surfaces and head-to-head two-choice tests in which the choices were two different repellents.…”
Section: Practical Field-relevant Assays To Evaluate Tick Repellentsmentioning
confidence: 99%